Mainstreaming the Value of Religious Moderation by Teachers in the Digital Era - Partono Nyanasuryanadi; Muqarranah Sulaiman Kurdi; Musyarrafah Sulaiman Kurdi; Pandu Adi Cakranegara; Dendi Pratama; Nilawati Nilawati (STAI Hubbulwathan Duri, 2023)
Digital space is currently being used as a propaganda tool for extremism in the name of religion, so efforts are needed to counter this influence. This study aims to analyze the mainstreaming of religious moderation by teachers in the digital era as an effort to counter the influence of intolerance and extremism. The research method used is Systematic Literature Review (SLR) with meta-synthetic data analysis techniques. Data was obtained through a collection of published journals from 2019-2022. According to the findings of this study, educators can promote religious moderation in today's digital age through a variety of activities, including 1) literacy through digital libraries; 2) literacy through social media; 3) literacy through webinars; and 4) literacy through scientific writing. In order to educate students about religious moderation and how it might be applied in a multicultural society's day-to-day activities, this literacy programme has been designed.